2021
DOI: 10.1021/acs.jpclett.1c01935
|View full text |Cite
|
Sign up to set email alerts
|

Unique Curve for the Radiative Photovoltage Deficit Caused by the Urbach Tail

Abstract: The photovoltage V oc of high-performance solar cells such as GaAs and metal halide perovskites is affected by the exponential Urbach tail in the absorption spectrum, with an energy parameter E U. It has been observed that increasing Urbach energy decreases the maximum photovoltage that can be achieved. On the basis of detailed balance and reciprocity of absorption and emission, we present a calculation that shows that the voltage loss due to the exponential tail in an absorption obeys a universal relation ΔV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(62 reference statements)
2
7
0
Order By: Relevance
“…This means that the relation between voltage loss and E U is independent of the absorber material’s bandgap in the case of E U < kT . Furthermore, recently, Bisquert reported a universal relation to quantify the photovoltage loss: Δ V OC rad = ( kT / q ) ln­(1 – E U / kT ), for E U < kT . For the absorber materials with more disorder ( E U > kT ), the band-filling effect becomes important in order to evaluate the radiative limits on the V OC and to examine realistic device performances.…”
mentioning
confidence: 99%
“…This means that the relation between voltage loss and E U is independent of the absorber material’s bandgap in the case of E U < kT . Furthermore, recently, Bisquert reported a universal relation to quantify the photovoltage loss: Δ V OC rad = ( kT / q ) ln­(1 – E U / kT ), for E U < kT . For the absorber materials with more disorder ( E U > kT ), the band-filling effect becomes important in order to evaluate the radiative limits on the V OC and to examine realistic device performances.…”
mentioning
confidence: 99%
“…The Urbach tail appears due to lattice disorder with introducing an exponential distribution of energy states near the optical band edges, 65 which eventually leads to energy loss by nonradiative charge recombination with sub-bandgap absorption. 66 Consequently, the increasingly generated defects in the perovskite film on NiO X are likely responsible for the severely deteriorated FF whereas the compressive strain induced by pTPD substrate effectively suppresses the defect formation and, thus, results in the consistent absorbance onset. 67,68 Normal XRD analysis was conducted for the aged full devices after finishing the long-term performance tracking for 911 h. The resulted XRD patterns are shown in Figure 5 and Figure S8 for full spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Especially, the absorption onset of the perovskite film on NiO X gets much broader as it is being aged, revealing a pronounced tailing of the absorption band. The Urbach tail appears due to lattice disorder with introducing an exponential distribution of energy states near the optical band edges, which eventually leads to energy loss by nonradiative charge recombination with sub-bandgap absorption . Consequently, the increasingly generated defects in the perovskite film on NiO X are likely responsible for the severely deteriorated FF whereas the compressive strain induced by pTPD substrate effectively suppresses the defect formation and, thus, results in the consistent absorbance onset. , …”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that this property leads to a rapid rise of the JDOS that is concurrent with a shortening of disorder correlations, which implies a sharpening of the distribution of band edges, a reduction of the number of thermally induced tail‐states and, by extension, a sharper optical absorption profile. Since the related Urbach tail determines the losses of open‐circuit voltage in the radiative limit, [ 78 ] this finding is potentially relevant for the design of solar materials. We have also contrasted these findings to the case of PbTe, a similarly anharmonic material also exhibiting resonant bonding and a similar electronic structure, but lacking the dynamic structural flexibility of the perovskite lattice as expressed in transversality.…”
Section: Discussionmentioning
confidence: 99%